Evaluación de la eficiencia de Tres Insecticidas para el Control de la Mosca de la Semilla (delia platura. meigen) de Chocho (lupinus mutabilis. sweet) por el mètodo de recubrimiento en el Barrio San Isidro Los Bancos, Parroquia Alaquez, Latacunga, Cotopaxi, 2019. - Suqui Carchi, Gloria Emperatriz (2019)
The research project was carried out in the San Isidro Los Bancos neighborhood, Aláquez Parish, Latacunga Canton, Cotopaxi Province, at an altitude of 3070 m.a.s.l. and coordinates 00º 51 '31' 'south latitude and 78º 34' 23 '' west longitude, with the objective of evaluating the efficiency of three insecticides for the seed fly control (Delia platura. Meigen) of chocho (Lupinus mutabilis Sweet) by the coating method. A randomized complete design was applied with a factorial arrangement of 3 x 3 + 2, giving a total of 11 treatments and 33 experimental units. The experiment was carried out in the laboratory and in the field; Germination tests were performed in the laboratory, determining 94.5% of germinated seed of L. mutabilis; Zeolite, cow dung, adherent polymer and Trichoderma spp. were used for the coating, incorporating insecticides to these coatings: Chlorpirifos + cypermetrin, Bacillus thurigiensis and molle flour (HAM). In the field phase it was proceded to delimit the land, form the grooves, for the planting 3 seeds were placed per blow. The indicators to be evaluated were: germination percentage (PG), emergency percentage (PE), emergency speed index (IVE), germination pest incidence percentage (PIG), emergency (PIE) and population density (PD). The following results were obtained: The T7-I3C1 treatment (Schinus molle L. 0.5 g / g) was the best in PG with 95.56%, PE with 90.60%; in the IVE the treatment T7-I3C1 with 4.83, in PIG the treatment T7-I3C1, obtained 2% and in PIE 0.67%; the population density of larvae and pupae of D. platura was high. Finally, the T7-I3C1 treatment shows the highest efficiency of 87.63% since the molle contains pinene and piperine it is recommended to use for the control of D. platura as an organic alternative.